2019
DOI: 10.1093/jamia/ocz074
|View full text |Cite
|
Sign up to set email alerts
|

A smart decision: smartphone use for operative data collection in arthroscopic shoulder instability surgery

Abstract: Objective This study tested validity, accuracy, and efficiency of the Orthopaedic Minimal Data Set Episode of Care (OME) compared with traditional operative report in arthroscopic surgery for shoulder instability. As of November 2017, OME had successfully captured baseline data on 97% of 18 700 eligible cases. Materials and Methods This study analyzes 100 cases entered into OME through smartphones by 12 surgeons at an institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…However, the OME data collection tool and resultant datasets have been previously validated for multiple surgical interventions and used in a growing number of contemporary studies. 7-12,15-17 Curtis et al 8 investigated the completion rates and agreement measures between OME- and EMR-based control datasets capturing peri/intraoperative details of primary total hip arthroplasty. The authors reported that the OME dataset demonstrated significantly higher completion rates in 41% of the evaluated variables.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the OME data collection tool and resultant datasets have been previously validated for multiple surgical interventions and used in a growing number of contemporary studies. 7-12,15-17 Curtis et al 8 investigated the completion rates and agreement measures between OME- and EMR-based control datasets capturing peri/intraoperative details of primary total hip arthroplasty. The authors reported that the OME dataset demonstrated significantly higher completion rates in 41% of the evaluated variables.…”
Section: Discussionmentioning
confidence: 99%
“…The OME dataset has been previously shown to provide reliable data for upper extremity surgery. Mohr et al 10 evaluated the OME completion and agreement between 100 surgical treatment cases of arthroscopic shoulder instability. Datapoints were recorded in the OME by 12 surgeons and compared with EMR-based dataset extracted by a blinded reviewer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations